ANALISIS KEMAMPUAN MEMBACA PESERTA DIDIK KELAS 2 SD DENGAN EGRA SEBAGAI ASESMEN DIAGNOSTIK DI KABUPATEN MUARA ENIM - Prastikawati, Fadilah; Harini, Bunda (Jurnal PGSD, 2024)
Analysis of the Reading Ability of 2nd Grade Elementary School Students with EGRA as a Diagnostic Assessment in Muara Enim Regency aims to describe the reading ability of 2nd grade  school students with EGRA as a diagnostic assessment in Muara Enim Regency. This research uses descriptive quantitative research methods. The data collection technique used was a reading diagnostic assessment test using EGRA (Early Grade Reading Assessment). The sample in this research was 287 2nd grade students  in Muara Enim Regency. The EGRA test carried out consists of several subtasks based on literacy components. namely oral comprehension, vocabulary, phonics, fluency, reading comprehension, and the alphabet. Based on the research results, the reading ability of 2nd grade  elementary school students in Muara Enim Regency, in the oral comprehension subtask of students is still low, the average student score is 1.68. In the Vocabulary subtask is good, the average score of students' vocabulary knowledge was 5.53. In the Phonics subtask is good, the average phonics score for meaningful words was 7.53 and the average phonics score for meaningless words was 6.36. In the subtask, students' fluency is still below the class standard, the average fluency score is 43.68 from the class standard of 60. In the reading comprehension subtask, students are still low, the average reading comprehension score is 1.29. In the alphabet knowledge subtask, students know letter names well but do not know letter sounds, the average alphabet knowledge of letter names is 42.32 and the average score for knowledge of alphabet sounds is 10.36.